Respuesta :
Hello!
You can multiply (x-12) and (x+4)
x * x = x^2
x * 4 = 4x
-12 * x = -12x
-12 * 4 = -48
Now we have
x^2 - 8x - 48 = 9
Subtract 9 from both sides
x^2 - 8x -57 = 0
Use the quadratic formula
This give use the answer of
x = 4 +[tex] \sqrt{72} [/tex]
Hope this helps!
You can multiply (x-12) and (x+4)
x * x = x^2
x * 4 = 4x
-12 * x = -12x
-12 * 4 = -48
Now we have
x^2 - 8x - 48 = 9
Subtract 9 from both sides
x^2 - 8x -57 = 0
Use the quadratic formula
This give use the answer of
x = 4 +[tex] \sqrt{72} [/tex]
Hope this helps!
Answer:
x = 4 + √73
Step-by-step explanation:
The given equation is ( x-12 ) ( x + 4 ) = 9
We will solve the equation first.
( x - 12 ) ( x + 4 ) = 9
x( x+4 ) - 12 ( x + 4 ) = 9 [ Distributive property ]
x² + 4x - 12x - 48 = 9
x² - 8x - 48 = 9
x² - 8x - 48 - 9 = 0
x² - 8x - 57 = 0
[ x² - 2 (4x) + 16 ] - 57 - 16 = 0
(x - 4)² - 73 = 0
(x - 4)² = 73
( x-4 )² = √73
x = 4 + √73
x = 4 + √73 is the answer.